Population Dynamics and Stock Assessment of Capoeta umbla (Heckel, 1843) in Lake Hazar, Elazig, Turkey - Coban, Mehmet Zulfu; Gunduz, Fatih; Demirol, Ferhat; Ornekci, Gurel Nedim; Karakaya, Gokhan; Turkgulu, Ibrahim; Alp, Ahmet (Central Fisheries Research Inst, 2013)
Population parameters such as growth, mortality rates, annual catch and stock size of Capoeta umbla (Heckel, 1843) population in Lake Hazar were investigated. Length and weight relationships of the population was W= 0.070xTL(2.39) (n= 364; R-2 = 0.95) and von Bertalanffy Growth Parameters were estimated as L-infinity= 53.77 cm; K= 0.16; t(0)=-1.84 and W-infinity= 957.38 g. Natural mortality rate (M) was 0.363 while fishing mortality (F) and total mortality rate (Z) were 0.349 and 0.712, respectively. Annual catch was 25721 kg (107544 individuals) and mean fish size was 28.7 cm (239.4 g). Estimated stock size based on mark and recapture method was 91601 kg (CI(95%): 85163-99061 kg) and 382627 individuals (CI(95%): 355736-413916 individuals). Stock size was also assessed by using length-based cohort analysis and was found to be 95256 kg (CI(95%): 55079-263225 kg) and 358105 individuals (CI(95%): 240251-868729 individuals). According to yield-biomass relationships, estimated maximum sustainable yield (MSY) was 27070 kg.
Elazi? Hazar gölü'nde Yaşayan capoeta umbla (Heckel, 1843)'nin stok tahmini ve populasyon Dinami?i
Keywords: Lake Hazar; Capoeta umbla; growth parameters; mortality rates; stock assessment